2004
DOI: 10.1111/j.1365-2966.2004.07314.x
|View full text |Cite
|
Sign up to set email alerts
|

  Sct-type pulsations in eclipsing binary systems: RZ Cas

Abstract: We present the results of a three‐continent multisite photometric campaign carried out on the Algol‐type eclipsing binary system RZ Cas, in which the primary component has recently been discovered to be a δ Sct‐type pulsator. The present observations include, for the first time, complete simultaneous Strömgren uvby light curves together with a few Crawford Hβ data collected around the orbital phase of the first quadrature. The new observations confirm the pulsational behaviour of the primary component. A detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…This raises the question whether their pulsation is different. Some of these stars have unusually short pulsation periods, e.g., the 22-minute period of RZ Cas (Rodríguez et al 2004). In fact, RZ Cas also shows a λ Boo-type abundance pattern (Narusawa et al 2006).…”
mentioning
confidence: 99%
“…This raises the question whether their pulsation is different. Some of these stars have unusually short pulsation periods, e.g., the 22-minute period of RZ Cas (Rodríguez et al 2004). In fact, RZ Cas also shows a λ Boo-type abundance pattern (Narusawa et al 2006).…”
mentioning
confidence: 99%
“…We therefore propose that the primary component is a δ Scuti pulsator. There are only a very few known normal δ Scuti stars that are members of detached eclipsing binary systems (see Rodríguez 2002;Rodríguez et al 2004). Recent investigations have demonstrated the existence of a group of A-F pulsating stars located in the δ Scuti instability strip and with the same observational characteristics as δ Scuti stars but in a different evolutionary stage.…”
Section: Discussionmentioning
confidence: 99%
“…non-radial modes with l = |m|); -during the eclipses, the components act as a spatial filter which causes phase and amplitude modulation of the nonradial mode and makes the mode identification more accurate (Mkrtichian et al 2002); -the pulsating component can be correctly identified if there is evidence that the pulsations are most clearly present during one of both minima. Rodríguez et al (2004) recently summarized the status of the eclipsing binaries with a δ Scuti component: only about a dozen cases are presently known. About 30% consist of eclipsing binaries with a classical δ Scuti pulsator while the rest defines a distinct class of δ Scuti pulsators, called the oscillating EA stars (Mkrtichian et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cepheids, for example, have been found in galactic EBs (Freyhammer et al 2005;Antipin et al 2007) as well as in the LMC (Alcock et al 2002;Lepischak & Welch 2004;Guinan et al 2005); there are more than 30 known δ-Scuti type components in EBs (see e.g. Dallaporta et al 2002;Rodríguez et al 2004;Christiansen et al 2007), and several other types such as slowly pulsating B stars (Pigulski & Michalska 2007;Pilecki & Szczygiel 2007 obtained with the HST Fine Guidance Sensor (Benedict et al 2002) that estimated its absolute magnitude of M = 0.61 ± 0.1.…”
Section: Introductionmentioning
confidence: 99%